Facing Climate Vulnerability in Mountain Areas: The Role of Rural Actors’ Agency and Situated Knowledge Production - Scotti, Ivano; Ievoli, Corrado; Bindi, Letizia; Bispini, Sara; Belliggiano, Angelo (Sustainability, 2023)
Climate change is challenging in mountain areas, and initiatives to define resilience programs appear essential to face global warming impacts. Despite the participatory strategy being primarily considered the best solution to involve local actors in adopting resilience actions, the literature stresses how mountain dwellers, like farmers, are often considered passive subjects, and their ability to understand climate change and the actions to adopt is inadequate. Based on this consideration, we aim to highlight the relevance of the mountain actors’ agency, their “lay” situated knowledge, and the epistemology for co-defining resilience actions. Adopting a “weak version” of the Actor-Network Theory as the research posture, we argue that farmers’ perceptions of climate vulnerability is based on their experience of it, and their resilience actions or suggestions are coherent with their endowment resources (financial and knowledge) and their position in the economic system. In this sense, local actors’ initiatives to face climate change can be limited by their specific position in the socioeconomic contest-related value chain and their specific relationship with local natural settings. A participative strategy to co-define resilience actions can help identify more effective initiatives according to the context between actors. Moreover, it can contribute to the knowledge exchange among “lay” local actors, experts, and policymakers, benefiting everyone; farmers could identify suitable solutions to face climate vulnerability, experts could increase their knowledge of local contexts, and policymakers could define adequate policies. Focusing on a specific area in “Alto Molise” (Italy), we present research results to contribute to the debate on climate resilience in mountain areas, stressing the significance of the local actors’ agency, the presence of the different epistemologies put in play (lay and expert ones), the co-production of knowledge, and the need to actively involve local actors in designing practices and policies to face climate change.